The ways of improving the efficiency of gas turbine plants based on aircraft gas turbine engines - Volianska, Larysa; Gvozdetskyi, Ivan; Fakhar, Mohammad (Science-based technologies, 2020)
Every year in the world, a large number of aircraft engines designed and manufactured throught ten to twenty years ago and spent their flight service life time on civil and military aircraft are decommissioned due to a decrease of their operational reliability. In the same time, the most of their structural units and parts still have significant safety margins and can be used as part of ground installations for various purposes. The level of parameters of the working process of these engines, and first of all, the compressor pressure ratio of the compressor and the temperature of the gases in front of the turbine, is relatively low, therefore the efficiency of such engines is relatively low, and therefore the fuel efficiency of such engines does not meet modern requirements.The problem of improving the fuel efficiency of stationary gas turbine plants based on aircraft engines that have exhausted their life on aircraft is urgent for several reasons. On the one hand, the cost of fuel is a significant part of the operating costs of the enterprises that use them, and adversely affects the economic performance of these enterprises. On the other hand, significant fuel consumption causes the formation of large quantities of combustion products, which are emitted into the atmosphere, polluting it. To solve this problem, in article it proposes to improve the working process of such power plants by Regeneration of the Heat of Exhaust Gases and preheating the fuel before it is fed into the combustion chamber. The purpose of this work is to evaluate the level of joint effect of heat recovery of the exhaust gases and the degree of preheating of the fuel on the fuel efficiency of gas turbine plants. The object of the study was a gas turbine plant based on an aircraft turbo engine that exhausted its flight life. It was proposed to add a dual heat exchanger into gas turbine plant to heat the compressed air before entering the combustion chamber and preheating the fuel. The calculations show that the combined effect of these two measures can significantly increase the internal efficiency of a gas turbine plant. The calculations were carried out taking into account changes in the thermophysical properties of air in the compressor and combustion products with changes in temperature as for real gases.